The Treatment of glomerulonephritis - Pusey, C. D (Kluwer Academic Publishers, 1999)
Glomerulonephritis is one of the commonest causes of end-stage renal failure worldwide. Although there have been considerable advances in the management of renal failure by dialysis and transplantation, there has been relatively little progress in its prevention. This volume sets out to review current practice in the treatment of glomerulonephritis, which is aimed both at controlling the clinical manifestations, e.g. nephrotic syndrome, and at preventing the progression to renal failure. The term glomerulonephritis covers a wide range of conditions with different immunological, histological and clinical features. This volume therefore starts with reviews of the immunology and pathology of different types of glomerulonephritis. This is followed by detailed consideration of the treatment of the commoner primary and secondary forms of the disease. There are separate chapters on special circumstances, such as glomerulonephritis in pregnancy or following renal transplantation. In each chapter, attempts are made to review the evidence for the effectiveness of treatment, based on controlled trials, immunopathological principles and the authors\' considerable experience. Although some aspects of the treatment of glomerulonephritis can be found in the standard texts on renal disease, this volume provides an up-to-date, thoroughly referenced, and practical guide to management. As such, it should be of value to nephrologists and general physicians, including those in training, and to postgraduate students of nephrology.
Developments in nephrology ; Vol. 40
Keywords: nefrologie; Glomerulonephritis; glomerulonefritida